Data Centric Data Object Caching System for DAN - V. Sujatha Lakshmi, Y. K. Sundara Krishna, G. K. Mohan Devarakonda (International Journal of Advanced Science and Technology, 2020)
Data Aware Networking is a prominent networking system in future networks to provide consistent Data Objects to the users in effective and efficient manner [7]. Data Objects in Data Aware Networking (DAN) are referred to as Named Data Objects (NDOs) which are identified with unique ID or with unique name. The Architecture of DAN primarily consists of NDO Publishers, DAN Agents and NDO Clients. DAN networking may also consist of DAN realms that are subgroups of DAN Agents belong to a group of NDOs/NDOs of potential domains as the case may be [1]. One who wants to publish an informative document shall make such informative document as NDO in a systematic way by following the procedures of DAN systems. Such persons are authors of the NDOs. The authors will publish their informative documents through NDO publishers so that NDOs can be available to all NDO clients through DAN. NDO Publisher may send such published NDOs to prominent probabilistic required DAN Agents in order to make them available to the enthusiastic NDO clients. NDO clients who wish to refer required NDO can access such NDO through nearby DAN Agents. While routing such NDOs, some of the interested DAN Agents may also cache the NDOs so that future requests are served from the copies of cached NDO instead of referring to the concerned NDO publisher. Two NDO caching methods are proposed in this paper viz., Reactive Caching Method, Proactive Catching Method. In Reactive Caching Method, NDOs are cached while serving the request of NDO client directly from the concerned NDO publisher. In Proactive Caching Method, the publisher of the NDO may also send copy of the NDO to the prominent probabilistic Data Agents in advance based on the statistical information available with the NDO Publisher. This paper proposes algorithms for Reactive Catching Method and Proactive Catching Method of NDO caching systems in DAN.